Modulation of Alpha-synuclein Expression and Associated Effects by MicroRNA Let-7 in Transgenic C. elegans - Shamsuzzama,; Kumar, Lalit; Nazir, Aamir (Frontiers in Molecular Neuroscience, 2017)
Abstract: Neurodegenerative Parkinson’s disease (PD) is a multi-factorial disorder for which a complete cure does not exist. Understanding the mechanism of initiation and progression of this disease has been quite challenging; however, progress has been made towards understanding certain genetic aspects related to the disease condition. Genetics studies have provided clues towards the role of microRNAs (miRNAs) in various disease conditions. One of the crucial miRNA molecules, Let-7, is highly conserved miRNA and is known to regulate important functions of development and viability. Altered expression of let-7 miRNA has been reported in C. elegans model of PD. We carried out studies with Let-7, employing transgenic C. elegans model expressing ‘human’ alpha-synuclein. We developed a let-7 loss-of-function model towards studying the downstream effects related to PD. We observed let-7 miRNA was up-regulated in C. elegans model of Parkinson’s disease. We figured that loss of let-7 miRNA leads to decreased alpha-synuclein expression, increased autophagy, increased Daf-16 expression, increased oxidative stress and increased lipid content with no effect on dopaminergic / acetylcholinergic neurons. Our findings indicate that let-7 miRNA regulates Parkinson’s disease-associated pathways. Our study provides insight towards the role of let-7 in regulating expression of genes associated with these pathways which might have implications on the multi-factorial nature of PD. Potential pharmacological agents modulating the expression of let-7 could be studied towards targeting the multi-factorial aspect of PD.